Improving Students’ Reading Skills by Using The Mind Mapping Technique at SMP N 5 Panyabungan in The Academic YearOf 2019/2020 - Sima, Syarifah (The Explora, 2020)
The nature of this study is action research. This study aimed at improving the students‟reading skills by using the mind map technique in the process of reading teaching and learning. This research consisted of two cycles. It was conducted collaboratively with the English teacher. The subjects of this research were 25 students of class IX 1 in SMP N 5 Panyabungan, Mandailing Natal. The data in this research were collected through observations, interviews, and documentations. The data were in the form of fieldnotes, interview transcripts, photographs, and students‟ portofolios. The researcher used qualitative method in analysing the data. The researcher also enhanced the trustworthiness of the data and the subjectivity by using the two forms of triangulation: timeand researcher triangulation.The result of the two cycles showed that the use of the mind map technique could improve the students‟ reading skills. The students gotimprovements in the paraphrasing sentence, finding topic sentence,and vocabulary mastery. Moreover, through the mind map technique, the students were motivated to be active in the classroom activities. They were actively involved in the process of teaching and learning. This condition stimulated the students to work based on their own actual capability. Thus, the students got more experiences and improved their achievement.